UTILIZATION OF TASK AUTOMATION TECHNOLOGIES BY PROFESSIONAL SECRETARIES FOR IMPROVED JOB PERFORMANCE IN PUBLIC ORGANIZATIONS IN EBONYI STATE (NAU Journal of Technology and Vocational Education, 2026)
This study examined the utilization of digital task automation technologies by professional secretaries for improved job performance in public organizations in Ebonyi State. One research question and one null hypothesis guided the study. The study adopted survey research design. A population of 527 professional secretaries in the 32 Ministries in Ebonyi State was studied using census survey method. A10-item structured questionnaire was used for data collection. Face and content validity of the instrument was ascertained using three experts in the field of education. The reliability of the instrument was established using pilot testing method and Cronbach alpha formula was used to calculate the internal consistence of the instrument with a reliability coefficient of .72 obtained. Mean, standard deviation and two-way analysis of variance (ANOVA) were used for data analysis. Findings revealed that professional secretaries in public organizations in Ebonyi State rarely utilized digital task automation technologies for improved job performance. It was also found that gender was not a significant factor on the extent professional secretaries utilize digital task automation technologies for improved job performance while years of working experience was a significant factor in this regard. The research concluded that professional secretaries in Ebonyi State's public organizations utilize digital automation technologies task for improved job performance at a low extent despite the potential improved utilization of digital task automation technologies. It was recommended that directors of public organizations in Ebonyi State should provide their professional secretaries with regular training in digital task automation technologies and access to these technologies. Organizing periodic workshops and seminars can help professional secretaries understand how automation can reduce repetitive tasks and improved job performance.
Keywords: Utilization; Digital Task Automation; Professional Secretaries; Job Performance